Gaze strategy and anticipation of defensive situations in youth performance soccer - an eye-tracking pilot study - Herden, M.; Adami, T.; Ehsani, B.; Schumacher, N. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In fast-paced team sports like soccer, defenders anticipation skills are crucial in decisions-making, often determining success or failure [1]. Studies show that expert athletes use more effective visual search strategies and focus on more relevant areas than less experienced athletes, implying that gaze behaviour such as saccades and fixations may be relevant for anticipation and successful decisions in soccer [2]. The aim of this pilot study was thus to investigate differences in gaze behaviour with correct or incorrect decisions in young elite soccer players. METHODS: The study enrolled 10 young elite soccer players, including six defenders and four offensive players aged 16-18 years, (16.7 ± 0.68) with an average of 11.2 years of soccer experience. Participants viewed standardized videos of 48 defensive 1:1 game situations which were occluded at -150, -300, and -450ms before the critical last ball contact. Study participants were instructed to decide within 10 seconds after occlusion whether the opponent player depicted in the video was about to run to the left or right. Gaze behaviour was registered with an Eye Tracking System (Tobii Pro Glasses 3) measuring total saccades and fixations. Fixations were analysed with respect to regions of interest defined by Krzepota et al [3]. Differences between correct and incorrect decisions with regard to total saccades and fixations were calculated using the Mann-Whitney-U Test. The alpha-level was set at 0.05. RESULTS: Significant differences were observed for total saccades (p = 0.026), fixations at the "zone-in front of-of the-ball/ foot" (p = 0.008), and the "zone beyond the player and ball" (p = 0.020) at -300ms while correct decisions showed more total saccades, shorter fixation duration at the "zone in front of the ball" and longer fixation duration at the "zone beyond the player and ball". Video sequences at occlusion timestamps of -150ms and -450ms revealed no significant differences between correct or incorrect decisions. CONCLUSION: The differences in gaze behaviour (saccades and fixations) underline their importance in correct decision-making. Young soccer players may make better decisions with respect to anticipated opponents` movement when they exhibit more saccades and shorter fixation duration at the "zone in front of the ball". Future research should explore integrating gaze strategies into training and further investigate the relationship between saccades, player position, and decision accuracy.